Space management of academic building (Politeknik Shah Alam) / Muhammad Shahreel Amizi Shamsuddin - Shamsuddin, Muhammad Shahreel Amizi (2017)
The “Universiti Teknologi MARA” (UiTM) owns and uses an extensive portfolio of land and building assets in delivering its teaching and research programmed. This document provides a policy and management framework to ensure that these assets are maintained appropriately to support the University’s strategic objective. UiTM is first university which created inventory audit system in Malaysia. Inventory audit at Universiti Teknologi Mara run by Rafulin FMS Sdn Bhd as the main contractor. In order to achieve the vision to become a world class university, one of the condition that need to be fulfilled is that they need to have quality in civil, mechanical and electrical for academic facilities. Infrastructures which support individual in organization to achieve their vision, academic facility play a vital role in public university vision to become a world class university. However, quality academic facilities should accompanied by efficient and effectively facility management system. An efficient facility management system is not only able to utilize the use of the facilities but also can help manage the resources needed in the management process.